Effective modification of photocatalytic and piezocatalytic performances for poly(heptazine imide) by carbon dots decoration. Issue 34 (15th August 2022) - Wang, Shijie; Zhang, Haoqing; Nie, Ran; Ning, Yuxin; Zhao, Chenxi; Xia, Zhonghui; Niu, Ping; Li, Li; Wang, Shulan
Abstract : This work provides an effective strategy to modify the photocatalytic and piezoelectric catalytic activities of poly(heptazine imide) (PHI) by decorating with a low amount of carbon dots. Abstract : As the high-crystalline phase of carbon nitride, poly(heptazine imide) (PHI) has attracted much attention in recent years, considering the more effective light absorption, better charge carrier behavior, and higher surface area of PHI compared with its counterpart with a melon structure that is commonly synthesized through thermal polymerization. Nevertheless, exploring effective strategies to further improve the performance of PHI is still highly desirable. In this work, it is revealed that the photocatalytic as well as piezocatalytic performances of PHI are greatly promoted by coupling with carbon dots (CDots) through a facile ultrasonication process. Detailed structure characterizations indicate that a very low content of CDots (0.05%) decoration can double the light absorbance and achieve the efficient separation and transfer of photogenerated charge carriers. The optimal photocatalytic hydrogen evolution rate of PHI/CDots is about 2.49 and 2.81 times that of PHI, under UV-Visible and visible light irradiation, respectively. Moreover, the piezocatalytic H2 O2 generation and KMnO4 degradation activities of PHI/CDots are around 2 times that of PHI. The results obtained in this work provide references for the modification of PHI and may inspire new strategies for the design of highly efficient carbonaceous photocatalysts.